Pengaruh Gaya Kepemimpinan dan Kepuasan Kerja Terhadap Kinerja Pegawai pada Dinas Sosial Kabupaten Enrekang - Wahyuni, Andi; Haerana, Haerana; Rasdiana, Rasdiana (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2023)
This study aims to determine the effect of leadership style and job satisfaction on employee performance in the Social Service of Enrekang Regency. The type of research used is quantitative research. Data collection techniques using observation and questionnaires with the number of respondents, namely all employees in the Social Service of Enrekang Regency as many as 37 people. Respondent's data were analyzed by simple linear regression using SPSS version 25 application. The results of this study indicate that partially the average acquisition (grand mean) of respondents' responses related to leadership style is 4.38 which is categorized as very good. Job satisfaction has a grand mean response of 4.39 which is also categorized as very good. Then based on the simultaneous test (F test) the calculated F value = 31.026 is greater than the F table value = 3.27 which means that simultaneously leadership style and job satisfaction have a positive and significant effect on employee performance at the Social Service of Enrekang Regency. The coefficient of determination (R square) obtained a coefficient of 64.6% which means that all independent variables namely leadership style and job satisfaction have a joint contribution (simultaneous) of 64.6% to the dependent variable, namely employee performance.